Improving Glycerol Photoreforming Hydrogen Production Over Ag2O-TiO2 Catalysts by Enhanced Colloidal Dispersion Stability - Yang, Zhi; Zhong, Weilin; Chen, Ying; Wang, Chao; Mo, Songping; Zhang, Jingtao; Shu, Riyang; Song, Qingbin (Frontiers in Chemistry, 2020)
Solar-driven photocatalytic reforming of biomass derived resources for hydrogen production offers a sustainable route towards the generation of clean and renewable fuels. However, the dispersion stability of the catalyst particles in the aqueous phase hinders the efficiency of hydrogen production. In this work, a novel method of mixing Ag2O-TiO2 photocatalysts with different morphologies was implemented to promote colloidal dispersion stability thereby improving hydrogen production performance. A series of Ag2O-TiO2 nanoparticles with different morphologies were synthesized and their dispersion stabilities in aqueous phase were investigated individually. Two types of Ag2O-TiO2 particles with different morphologies under certain proportion were mixed and suspended in glycerol aqueous solution without adding any dispersant for enhancing dispersion stability while reacting. From the results, photocatalytic hydrogen production was found to be strong correlated to colloidal dispersion stability. The mixed suspension of Ag2O-TiO2 nanosphere and nanoplate achieved an excellent colloidal dispersion stability without employing any additives or external energy input, and the photoreforming hydrogen production obtained from this binary component system was around 1.1-2.3 times higher that of the single component system. From the calculated hydrogen production rate constants between continuous stirring and the binary system, there was only less than 6% differences suggesting an efficient mass transfer of the binary system for photoreforming hydrogen production. The proposed method could provide some inspiration to a more energy-efficient heterogeneous catalytic hydrogen production process.